2023
DOI: 10.3390/nano13152196
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of 3C/4H-SiC Nanowires by Molecular Dynamics Simulation

Kaili Yin,
Liping Shi,
Xiaoliang Ma
et al.

Abstract: Silicon carbide (SiC) is a promising material for thermoelectric power generation. The characterization of thermal transport properties is essential to understanding their applications in thermoelectric devices. The existence of stacking faults, which originate from the “wrong” stacking sequences of Si–C bilayers, is a general feature of SiC. However, the effects of stacking faults on the thermal properties of SiC are not well understood. In this study, we evaluated the accuracy of Tersoff, MEAM, and GW potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…However, SiC also contains 12% ionic bonds; thus, interatomic potentials like Tersoff are unable to accurately describe the optical branches, and the TA branch tends to be overestimated [ 19 ]. Previous research found that T90 potential can describe the acoustic branch of phonons well [ 35 ], but the acoustic branches obtained using Vashishta, EDIP, and MEAM potentials agree well with the DFT curves. Among them, the frequencies of the optical branches from Vashishta potential are in the same frequency range as those from DFT.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…However, SiC also contains 12% ionic bonds; thus, interatomic potentials like Tersoff are unable to accurately describe the optical branches, and the TA branch tends to be overestimated [ 19 ]. Previous research found that T90 potential can describe the acoustic branch of phonons well [ 35 ], but the acoustic branches obtained using Vashishta, EDIP, and MEAM potentials agree well with the DFT curves. Among them, the frequencies of the optical branches from Vashishta potential are in the same frequency range as those from DFT.…”
Section: Resultssupporting
confidence: 63%
“…Overall, none of the interatomic potentials show imaginary frequencies when describing phonon dispersion curves. Some of the outcomes of interatomic potentials exhibit slight variations compared with previous research results [35], which are likely attributed to differences in the selected model sizes. To further investigate the accuracy of the dispersion curves, Table 7 summarizes the phonon frequencies at high-symmetry points for 3C-SiC.…”
Section: Phonon Dispersion Curvecontrasting
confidence: 57%
See 3 more Smart Citations